2022
DOI: 10.3390/d14050324
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Genome of Salvia Sect. Drymosphace: Comparative and Phylogenetic Analysis

Abstract: Sect. Drymosphace is one of eight sections of Salvia subg. Glutinaria and includes 13 species and one dubious species that hold great economic value. Although the section is well supported, interspecific relationships remain unresolved. Moreover, most of this section’s plastome information remains unknown. In this study, we sequenced and assembled eight sect. Drymosphace plastomes and conducted comparative analyses within this section. The length of plastid genome sequences ranged from 151,330 bp to 151,614 bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 86 publications
2
5
0
Order By: Relevance
“…Previous studies have revealed that the expansion and contraction of the IR, LSC, and SSC regions are common during evolution and are the main reason for variations in plastome size ( Ravi et al., 2007 ; Downie and Jansen, 2015 ; Daniell et al., 2016 ). Significant contraction of IR region was observed among Linderniaceae species ( Supplementary Figure 2 ), which was also common in Lamiales, such as Gesneriaceae ( Gu et al., 2020 ), Lamiaceae ( Su et al., 2022 ), Oleaceae ( Long et al., 2023 ), Plantaginaceae ( Xie et al., 2023 ), and Scrophulariaceae ( Wang et al., 2022 ). Notably, the IR boundaries did not coincide exactly in the three populations of L. polygonoides , but they had the same plastome size.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies have revealed that the expansion and contraction of the IR, LSC, and SSC regions are common during evolution and are the main reason for variations in plastome size ( Ravi et al., 2007 ; Downie and Jansen, 2015 ; Daniell et al., 2016 ). Significant contraction of IR region was observed among Linderniaceae species ( Supplementary Figure 2 ), which was also common in Lamiales, such as Gesneriaceae ( Gu et al., 2020 ), Lamiaceae ( Su et al., 2022 ), Oleaceae ( Long et al., 2023 ), Plantaginaceae ( Xie et al., 2023 ), and Scrophulariaceae ( Wang et al., 2022 ). Notably, the IR boundaries did not coincide exactly in the three populations of L. polygonoides , but they had the same plastome size.…”
Section: Discussionmentioning
confidence: 91%
“…Five hypervariable regions were screened within the Linderniaceae, namely petN-psbM , rps16-trnQ , rpl32-trnL , rpl32 , and ycf1 , of which petN-psbM and rps16-trnQ were located in the LSC region and others were distributed in the SSC region. These non-coding regions have exhibited high nucleotide diversity and phylogenetic utility in Lamiales, such as petN-psbM in Lamiaceae ( Su et al., 2022 ; Wang et al., 2023 ), rps16-trnQ in Scrophulariaceae ( Dong et al., 2022 ) and Gesneriaceae ( Gu et al., 2020 ), and rpl32-trnL in Bignoniaceae ( Fonseca and Lohmann, 2018 ), Lamiaceae ( Hu et al., 2020 ) and Scrophulariaceae ( Dong et al., 2022 ). Furthermore, the gene ycf1 , the second largest gene in the plastid genome playing a critical role in plant cell survival ( Drescher et al., 2000 ), has been proposed as the most potential DNA barcode due to its high variability in land plants ( Drew and Sytsma, 2011 ; Dong et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…East Asia, in particular, stands out as significant hub of Salvia diversity, housing approximately 100 species. Remarkably, China alone is home to over 80 distinct species ( Wu, 1977 ; Hu et al., 2018 ; Su et al., 2022 ). Recent years have witnessed the discovery of new species within China, further enriching the genus’s diversity ( Hu et al., 2014 ; Wang et al., 2016 ; Xiang et al., 2016 ; Hu et al., 2017 ; Wei et al., 2019 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed the discovery of new species within China, further enriching the genus’s diversity ( Hu et al., 2014 ; Wang et al., 2016 ; Xiang et al., 2016 ; Hu et al., 2017 ; Wei et al., 2019 , 2021 ). The vast morphological diversity, spanning root to stamen, coupled with varied habitats, makes taxonomic studies of East Asian Salvia a formidable challenge ( Wei et al., 2015 ; Su et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation